A rare functional cardioprotective APOC3 variant has risen in frequency in distinct population isolates. - Tachmazidou, I; Dedoussis, G; Southam, L; Farmaki, A; Ritchie, G; Xifara, D; Matchan, A; Hatzikotoulas, K; Rayner, N; Chen, Y; Pollin, T; O'Connell, JR; et al. (Nature Publishing Group, 2013)
Isolated populations can empower the identification of rare variation associated with complex traits through next generation association studies, but the generalizability of such findings remains unknown. Here we genotype 1,267 individuals from a Greek population isolate on the Illumina HumanExome Beadchip, in search of functional coding variants associated with lipids traits. We find genome-wide significant evidence for association between R19X, a functional variant in APOC3, with increased high-density lipoprotein and decreased triglycerides levels. Approximately 3.8% of individuals are heterozygous for this cardioprotective variant, which was previously thought to be private to the Amish founder population. R19X is rare (<0.05% frequency) in outbred European populations. The increased frequency of R19X enables discovery of this lipid traits signal at genome-wide significance in a small sample size. This work exemplifies the value of isolated populations in successfully detecting transferable rare variant associations of high medical relevance.